الفكر الحداثي في الساحة النقدية العربية وموقف "عبد الملك مرتاض" منه - مصباحي, علي (University of Eloued جامعة الوادي, 2021)
في ظل الاحتكاك الثقافي بين النقاد العرب والغرب والبعثات العلمية المُتبادلة حدث تلاقح في الأفكار والمعارف فظهر على الساحة النقدية العربية المعاصرة الفكر الحداثي أو ما اصطلح عليه بالحداثة " التي انتشرت بين بريق لها عند بعض النقاد وعُتمة عند الآخرين ، بين قبول ونفور ،وبين تأييد وإنكار ، فالحداثيون يدعون إلى التغيير المُستمر في كل شيء ولا شيء عندهم ثابت حتى أن "رولان بارت" أعتبرها زلزالا حضاريا عنيفا ، وانقلابا ثقافيا شاملا لم يتوصل الإنسان المعاصر إلى السيطرة عليه ؛إذ هي موقف عام وشاملا ومعارض للثقافات التقليدية وفي ظل هذا الوافد الجديد إلى البيئة العربية المعاصرة تصدع معسكر النقاد العرب وانقسم إلى ثلاثة اتجاهات كبرى هي: الاتجاه الأول هم الحداثيون واعتبروا إن الحداثة حركة تنويره في الثقافة العربية وبداية مشروع نهضوي يُحقق أمل الشعوب ودعا هذا الاتجاه تبني الفكر الغربي وما يحتويه من نظريات ومعارف ومنهاج نقدية ،ويأتي على رأس هؤلاء "أحمد خالد سعيد الملقب بـ"أدونيس" أما الاتجاه الثاني فهم أنصار التراث ونادى هؤلاء إلى الالتزام والتشبث به، والذود عنه من حملات التغريب المسعورة، وأنصار هذا الاتجاه هم أصحاب الرؤية الدينية الأصولية ويأتي على رأسهم "أنور الجندي " و"محمد أركون " و"نبيل سليمان " أما أصحاب الاتجاه الثالث هم أصحاب النظرة التوفيقية ونادي هؤلاء إلى مسايرة تطور الفكر الغربي ومعارفه والاستفادة منه وانتقاء ما يصلح لخدمة التراث العربي الزاخر كمناهج نقدية ونظريات حديثة وآليات نقدية معاصرة دون إهمال للتراث العربي الزاخر بالكنوز و المعارف التي تمثل الهوية وارث الأجداد . فأين يقف عبد الملك مرتاض من هذه الاتجاهات الثلاثة؟ وما هو موقفه من الحداثة وبريقها الذي سطع على العيون؟ In light of the cultural friction that happened between the Arab and Western critics, and the mutual exchange of scholarship and knowledge, Modernism was born. Like most schools of thoughts, modernism was very well received among some and rejected by others. And between acceptance and refusal, supporting and denying; moderns are calling for constant change in everything for nothing is fixed. Roland Barthes considered it as a violent modern earthquake and a sweeping cultural transgression that modern man cannot control; it is a general attitude and an antithesis to traditional cultures In the context of this newcomer to the contemporary Arab environment, the Arab critics' camp cracked and split into three major trends: The first trend is the modernists: they considered modernism as an enlightenment movement in the Arab culture and the beginning of a Renaissance project to achieve the hope of the people and called to adopt Western thought and its content of theories, knowledge and critical approaches, and comes at the head of these "Ahmed Khaled Said, known as " Adonis " The second trend. Represented in the support of the heritage and called to adhere to it, and protect it from the campaigns of Westernization, and supporters of this trend are the owners of the religious vision of fundamentalism, represented by "Anwar soldier" and "Mohammed Arkoun" and "Nabil Suleiman". The third trend supporters are the owners of a conciliatory view. These call at keeping pace with the development of Western thought and its knowledge and benefiting from it, selecting what works to serve the rich Arab heritage as a critical curriculum, modern theories and contemporary monetary mechanisms without neglecting the Arab heritage; that is rich in treasures and knowledge that represent the identity and ancestral heritage. What…… "Abd El-Malek Mortad"position toword sthese thmee trends and what is his view toworods modernization and its enlihtenment.
مداخلة. الملتقى الدولي: النص التراثي العربي في منظورات الحداثة وما بعدها، الحدود، التصورات، الإشكالات. كلية الآداب واللغات. جامعة الشهيد حمه لخضر – الوادي
Keywords: التراث- الحداثة- عبد الملك مرتاض – النقد- الغرب; Modernity- Heritage-Abdul Malik Mortad- criticism- Western